2017
DOI: 10.1021/acs.jpcb.7b10933
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Li+ in Concentrated Ethylene Carbonate Solutions Studied by Low-Frequency Raman Scattering and Neutron Diffraction with 6Li/7Li Isotopic Substitution Methods

Abstract: Isotropic Raman scattering and time-of-flight neutron diffraction measurements were carried out for concentrated LiTFSA-EC solutions to obtain structural insight on solvated Li as well as the structure of contact ion pair, Li···TFSA, formed in highly concentrated EC solutions. Symmetrical stretching vibrational mode of solvated Li and solvated Li···TFSA ion pair were observed at ν = 168-177 and 202-224 cm, respectively. Detailed structural properties of solvated Li and Li···TFSA contact ion pair were derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 63 publications
8
33
0
Order By: Relevance
“…This result could be interpreted as a change in the oscillator strength of TDI − and the different ion pairs, but DFT computations show that the oscillator strength is similar for TDI − as a free ion, SSIP, and CIPs with different carbonates (see the Supporting Information). Thus, the appearance of the high-frequency band shows that the structure of the organic carbonate affects the formation of contact ion pairs, which is in agreement with previous studies. , In particular, it shows that CIP species are more prevalent in linear carbonates, which differs with other anions such as hexafluorophosphate (PF 6 – ) ions and bis­(trifluoromethanesulfonyl)­imide (TFSI – ) ions at the same concentrations. ,,, Moreover, it has been previously shown that the charge delocalization of the anion is not sufficient to avoid a strong interaction with the cation. For example, the thiocyanate anion (SCN – ) also shows a strong interaction with cations of different sizes and charge density in various environments, even though it has a relatively delocalized charge and it is on the extreme of the Hofmeister series. ,,, …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result could be interpreted as a change in the oscillator strength of TDI − and the different ion pairs, but DFT computations show that the oscillator strength is similar for TDI − as a free ion, SSIP, and CIPs with different carbonates (see the Supporting Information). Thus, the appearance of the high-frequency band shows that the structure of the organic carbonate affects the formation of contact ion pairs, which is in agreement with previous studies. , In particular, it shows that CIP species are more prevalent in linear carbonates, which differs with other anions such as hexafluorophosphate (PF 6 – ) ions and bis­(trifluoromethanesulfonyl)­imide (TFSI – ) ions at the same concentrations. ,,, Moreover, it has been previously shown that the charge delocalization of the anion is not sufficient to avoid a strong interaction with the cation. For example, the thiocyanate anion (SCN – ) also shows a strong interaction with cations of different sizes and charge density in various environments, even though it has a relatively delocalized charge and it is on the extreme of the Hofmeister series. ,,, …”
Section: Discussionsupporting
confidence: 89%
“…While the preferential solvation by organic carbonates is an extensively studied topic, the role of the mixed solvation shell in the speciation of Li + is a topic vastly unexplored. So far, most studies have focused on either lithium hexafluorophosphate (LiPF 6 ) or lithium bis­(trifluoromethanesulfonyl)­imide (LiTFSI), ,,, but the lack of simple vibrational modes in PF 6 − and TFSI − has complicated their analysis and interpretation. ,,, Thus, this study focuses on the effect of carbonate structure and composition on the speciation of lithium 4,5-dicyano-2-(trifluoromethyl)­imidazole salt (LiTDI, Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…These values seem slightly shifted to higher wavenumber region compared to previously reported Raman shifts of LiFSI in other solvents, presumably due to the low donating nature of NM. Raman spectra of LiTFSI/NM were successfully deconvoluted by assuming two peaks assigned to bound species (749 cm –1 ) and SSIP (742 cm –1 ), which are in good agreement with reported data …”
supporting
confidence: 87%
“…The in solution structure of inorganic Li salts has been studied extensively in the field of lithium ion batteries. Raman spectroscopy is specifically useful for this purpose, and many researchers have proposed that lithium salts change their form from a solvent‐separated ion pair (SSIP) to a contacted ion pair (CIP) and an aggregate (AGG) species at higher concentrations (Figure ) . SSIP is also referred to as free species, whereas CIP and AGG are referred to as bound species (Figure ).…”
mentioning
confidence: 99%
See 1 more Smart Citation